Study of Urban Rail Train Renewable Braking Energy Feedback System - JI Hui; LI Kunpeng; YI Yunlan (机车电传动)
In order to verify the function and reliability of urban rail train renewable energy feedback system, mathematical model of energy feedback converter with double-loop control strategy and SVPWM modulation was built, and the simulation and test were brought out. The results showed that the renewable energy feedback system could maintain the DC bus voltage steady and ensure the safety of the train, as well as realize braking energy feeding back to the grid with good quality.